Ayat-Ayat Imajinasi dalam Al-Qur’an: Sebuah Tafsir Tematik - Muh. Asyraf Syakur; Achmad Abubakar; Muhsin Mahfudz (Journal of Innovative and Creativity, 2025)
This study aims to explore the Qur’anic conception of imagination by analyzing the terms khayala (خيل) and ṣawwara (صوّر). The research seeks to determine whether these expressions are related to Allah SWT, to human beings, or to the nature of reality as a whole. The research employs a qualitative approach using the methods of tafsir (Qur’anic interpretation) and philosophy. These approaches serve as the main analytical tools to uncover the essence of imagination within the Qur’an. The analysis is further supported by contemporary philosophical theories that help strengthen and contextualize the interpretation. Results. The study finds that the Qur’an presents imagination as a hierarchical concept encompassing divine, cosmic, and human dimensions. Allah SWT, as al-Muṣawwir (ٱلْمُصَوِّر), is depicted as engaging in an act of divine imagination that manifests all of creation, reflected in the term ṣawwara (صوّر). The Qur’an also portrays reality as multilayered and ever-evolving, represented by ṣuwar (صوَر) and yuṣawwiru (يصوّر), encompassing both physical-biological and social-psychological realms. Furthermore, through the use of yukhayyalu (يخيل), human imagination is shown to operate within the vast expanse of Divine imagination, suggesting that all human creativity exists within God’s greater imaginative reality. The Qur’an views imagination not as a mere mental faculty but as a fundamental ontological principle that structures existence. Divine, cosmic, and human imaginations are interrelated in a continuous process of creation and re-creation. Thus, imagination in the Qur’anic perspective reflects the dynamic interplay between the Divine act of creation and human participation within that imaginative reality.